Analysis of Economic Growth Core and Periphery: Evidence from Aceh Province, Indonesia - Risnasari Risnasari; Abd. Jamal; Sofyan Syahnur (International Journal of Quantitative Research and Modeling, 2022)
This research is to determine factors that influenced Gross Regional Development Product (GRDP) Banda Aceh and Lhokseumawe city in context relationship between core and periphery using panel data regression of 23 districts/cities in Aceh Province, Indonesia year 2010-2020. Selected independent variables in this paper are GRDP core and periphery, population, distance between core and periphery, availability of hospital, availability of university and availability of industry. Based on estimation results, all independent variabels have significant effect toward GRDP Banda Aceh and Lhokseumawe city. Variabels that found have positive effect toward GRDP Banda Aceh city are GRDP core and periphery, and distance between core and periphery. Variabels that found have negative effect toward GRDP core Banda Aceh city are population, availability of hospital, availability of university and availability of industry. Then, variabels that found have positive effect toward GRDP Lhokseumawe city are GRDP core and periphery, distance between core and periphery, and availability of university. Variabels that found have negative effect toward GRDP core Lhokseumawe city are population, availability of hospital, and availability of industry. It is hoped that this findings will provide useful information for policymakers in attempt to enhance the competitiveness of regional economy.